Women as Passive Citizens in Kant's Theory of Citizenship - Durğun, Serpil (My University, 2020)
Kant, who is one of the contractarian theorists in political philosophy, positions the person who has the right to vote and participates in the legislative process as a citizen. This positioning is directly related to Kant's attribution of citizenship to the independence precondition. For Kant, independence means that a person possesses a certain amount of ownership that enables him to sustain his life on his own. The person who owns a certain quantity of property is the master of himself as he will not receive orders from the others and will not need the protection of others. Positioning an independent person as an active citizen with political rights, Kant considers persons who are non-owners as passive citizens because they cannot meet the prerequisite for independence. Passive citizens who are deprived of all political rights are merely citizens of the state. According to Kant's argument, women can never move up to the active citizenship status, although the republic has cleared the way for the possibility that every member of the republic could eventually move up to the active citizenship status. The status of being a man of property, which is a prerequisite for the independence criterion, loses all its functions when women are in question. Even if a woman is a property owner, this is still considered insufficient for the independence criterion. Kant bases his idea on the assumption of women's nature and the prenuptial agreement.

Siyaset felsefesinde sözleşmeci teorisyenlerden biri olan Kant, yasama işlerinde yasaların yapılmasına iştirak eden, oy hakkına sahip olan kişiyi vatandaş olarak konumlandırır. Bu konumlandırma, Kant’ın vatandaşlığı bağımsızlık önkoşuluna dayandırmasıyla doğrudan ilişkilidir. Kant için bağımsızlık, kişinin hayatını kendi kendine idame ettirebilmesini sağlayan belli bir miktarda mülkiyete sahip olması anlamına gelir. Belli miktarda mülkiyete sahip olan kişi, başka birisinden emir almayacağından ve başkalarının korumasına da muhtaç olmayacağından kendi kendisinin efendisi durumundadır. Bağımsız kişiyi politik haklara sahip etkin vatandaş olarak konumlandıran Kant, mülk sahibi olmayanları bağımsızlık önkoşulunu sağlayamadıklarından edilgin vatandaş olarak görür. Tüm politik haklardan mahrum olan edilgin vatandaşlar devletin sadece uyruğudurlar. Kant, cumhuriyetin her üyesinin zamanla etkin vatandaşlık statüsüne yükselebilme ihtimalinin önünü açık tutmasına karşın, kadınların hiçbir zaman etkin vatandaşlık statüsüne yükselemeyeceklerini savunur. Bağımsızlık kriterinin önkoşulu olan mülk sahibi olma, kadın söz konusu olduğunda tüm işlevini yitirir. Kadın mülk sahibi olsa bile yine de bağımsızlık kriteri için yetersiz görülür. Kant bu düşüncesini, kadın doğası varsayımı ve evlilik sözleşmesi üzerinden temellendirir.
Kant’ın Vatandaşlık Teorisinde Edilgin Vatandaş Olarak Kadın